The Wayward Bus Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Camille Oaks (Jayne Mansfield) rest her head on Ernest Horton's (Dan Dailey) shoulder. Elliott Pritchard (Larry Keating) in background, having just noticed Oaks's image in magazine. RESTRICTED USE_x000B_